THE IMPORTANCE OF USING INTERACTIVE METHODS IN TEACHING THE RUSSIAN LANGUAGE IN THE HIGHER EDUCATION SYSTEM - Shoniyozova Sadokat Nazarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The use of modern interactive teaching methods is a prerequisite for improving the process of teaching Russian as a foreign language in accordance with modern educational standards. The article presents some interactive methods and techniques that contribute to the development of students’ competence.Arousing interest in your subject, maintaining student motivation, making the lesson interesting and effective in terms of mastering the material covered is not an easy task. However, there are many different pedagogical approaches to address this issue. Consider one of these methods - interactive learning.